Oxidative Stress Modulates the Nitric Oxide Defense Promoted by Escherichia coli Flavorubredoxin - Baptista, Joana M. (American Society for Microbiology, 2012)
Mammalian cells of innate immunity respond to pathogen invasion by activating proteins that generate a burst of oxidative and nitrosative stress. Pathogens defend themselves from the toxic compounds by triggering a variety of detoxifying enzymes. Escherichia coli flavorubredoxin is a nitric oxide reductase that is expressed under nitrosative stress conditions. We report that in contrast to nitrosative stress alone, exposure to both nitrosative and oxidative stresses abolishes the expression of flavorubredoxin. Electron paramagnetic resonance (EPR) experiments showed that under these conditions, the iron center of the flavorubredoxin transcription activator NorR loses the ability to bind nitric oxide. Accordingly, triggering of the NorR ATPase activity, a requisite for flavorubredoxin activation, was impaired by treatment of the protein with the double stress. Studies of macrophages revealed that the contribution of flavorubredoxin to the survival of E. coli depends on the stage of macrophage infection and that the lack of protection observed at the early phase is related to inhibition of NorR activity by the oxidative burst. We propose that the time-dependent activation of flavorubredoxin contributes to the adaptation of E. coli to the different fluxes of hydrogen peroxide and nitric oxide to which the bacterium is subjected during the course of macrophage infection.